(3QSGdI aj (B"(3Efj CMeO Gddg(B"s - (3LeGd GdOjf CHh YHO Gddg,J (B761 (3g` s
(3ChdgG (B:s
(3bGd GdTjN PcQ GdSgjdj aj GdQhV GdCfa eSCdI aj GdfMh bGd(B: (3PcQgG SjHhjg hGHf GdSQGL s
(3BNQgG (B:s
(3hGdEaGOI dG GdJTfjY hMSHc ef GdbdGOI eG CMGW HGdLHjd jJdhg GdcdGe Ydi eSCdI GdGSJagGe ddTjN GdYdGeI SjHhjg ChGfg GHf gTGe s
(3Vef eLehY , JQJjHgG (B: (3ef U (B239 - (3U(B246s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B23 ; (3HQhcdeGf edMb (B- (3GdLRA (B2 - (3U (B16 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 - (3U (B132 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK , JQeje s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdfMhs